Safely through the Gate: Exploring Media Coverage and Journalists Decisions on the Flow of Farm Safety Stories - Rebecca Swenson; Brandon Roiger; Alexis Murillo (Journal of Applied Communications, 2018)
Agriculture continues to rank as one of the most dangerous industries in the nation. Media coverage is an important tool for sharing farm safety information, improving knowledge and changing behaviors. Despite this importance, surprisingly little research has focused on agricultural media coverage and the forces that influence journalists’ decisions about when and how to cover safety stories. This study uses content analysis methods to examine the nature of farm safety issues, accidents, and topics that appear in mainstream news, agricultural media, and blogs. Researchers also interviewed journalists and bloggers to better understand their motivations, barriers, and information needs when covering safety topics. Findings indicate there is a need to expand safety reporting beyond accident coverage and to better engage bloggers in farm safety topics. Journalists emphasized their strong moral obligation to cover farm safety and desire to include more preventative information and actionable advice in stories. They also described their struggle to find local angles other than accident reports and to find timely hooks for farm safety features outside of harvest and planting seasons. Journalists wanted more research-based studies, stories, and relationships with organizational experts connected to safety and health issues. Few bloggers were engaged with farm safety topics, as some preferred to focus on more consumer-oriented information or felt they did not know enough about farm safety to write about it. Recommendations are included for journalists and organizations working on farm safety related topics and campaigns.
Keywords: Farm Safety; Agricultural Communication; News; Journalism; Blogs